The effect of flexible joint-like elements on the adhesive performance of nature-inspired bent mushroom-like fibers - Geikowsky, Elliot; Gorumlu, Serdar; Aksak, Burak (Beilstein Journal of Nanotechnology, 2018)
Many organisms rely on densely packed, tilted and curved fibers of various dimensions to attach to surfaces. While the high elastic modulus of these fibers enables an extremely large number of fibers per unit area, where each fiber stands freely without sticking to its neighbors, the tilt/curvature provides them with the compliance and the directional adhesion properties to attach strongly and efficiently to a surface. Recent studies have revealed that many of such organisms also feature materials with a graded elastic modulus that is tailored towards improving the contact area without sacrificing the fiber density. In particular, for male ladybird beetles, research has shown that the adhesive setae feature a material gradient such that the elastic modulus of the material at the junction between the stalk and the divergent distal end is close to minimum. This soft material acts like a flexible joint, improving the bending compliance of the tip. Here, we mimic this feature using tilted, mushroom-like, stiff fibers comprised of a stiff stalk of elastic modulus 126 MPa, a softer tip of elastic modulus 8.89 MPa, and a joint-like element of elastic modulus 0.45 MPa (very soft), 8.89 MPa (soft), or 126 MPa (stiff) in between. The results from load–drag–pull (LDP) experiments performed along (gripping) and against (releasing) the tilt direction indicate that the soft and the very soft joint fibers performed superior to the stiff joint fibers and maintained directionally dependent performance. The soft joint fibers achieved up to 22 kPa in shear and 110 kPa in pull-off stress in the gripping direction, which are twice and ten times higher than that in the releasing direction, respectively. A model to optimize the elastic modulus of the joint-like elements to enable sliding without peeling of the tips has been proposed.
Keywords: bent fibers; bioinspired dry adhesives; gecko adhesion; joint-like element; mushroom-like fibers

(untitled) - Federle, W. (J. Exp. Biol., 2006)

(untitled) - Arzt, E.; Gorb, S.; Spolenak, R. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Autumn, K.; Liang, Y. A.; Hsieh, S. T.; Zesch, W.; Chan, W. P.; Kenny, T. W.; Fearing, R.; Full, R. J. (Nature, 2000)

(untitled) - Varenberg, M.; Pugno, N. M.; Gorb, S. N. (Soft Matter, 2010)

(untitled) - Persson, B. N. J. (Wear, 2003)

(untitled) - Persson, B. N. J. (J. Chem. Phys., 2003)

(untitled) - Gao, H.; Ji, B.; Buehler, M. J.; Yao, H. (Mech. Chem. Biosyst., 2004)

(untitled) - Russell, A. P. (Can. J. Zool., 1986)

(untitled) - Autumn, K.; Majidi, C.; Groff, R. E.; Dittmore, A.; Fearing, R. (J. Exp. Biol., 2006)

(untitled) - Autumn, K.; Sitti, M.; Liang, Y. A.; Peattie, A. M.; Hansen, W. R.; Sponberg, S.; Kenny, T. W.; Fearing, R.; Israelachvili, J. N.; Full, R. J. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Hu, C.; Alex Greaney, P. (J. Appl. Phys., 2014)

(untitled) - Autumn, K.; Dittmore, A.; Santos, D.; Spenko, M.; Cutkosky, M. (J. Exp. Biol., 2006)

(untitled) - Kim, T.-i.; Jeong, H. E.; Suh, K. Y.; Lee, H. H. (Adv. Mater., 2009)

(untitled) - Aksak, B.; Murphy, M. P.; Sitti, M. (Langmuir, 2007)

(untitled) - Jeong, H. E.; Lee, J.-K.; Kim, H. N.; Moon, S. H.; Suh, K. Y. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Murphy, M. P.; Aksak, B.; Sitti, M. (Small, 2009)

(untitled) - Lee, J.; Fearing, R. S.; Komvopoulos, K. (Appl. Phys. Lett., 2008)

(untitled) - Wang, Z. (ACS Nano, 2018)

(untitled) - Mengüç, Y.; Yang, S. Y.; Kim, S.; Rogers, J. A.; Sitti, M. (Adv. Funct. Mater., 2012)

(untitled) - Santos, D.; Spenko, M.; Parness, A.; Kim, S.; Cutkosky, M. (J. Adhes. Sci. Technol., 2007)

(untitled) - Northen, M. T.; Greiner, C.; Arzt, E.; Turner, K. L. (Adv. Mater., 2008)

(untitled) - Jin, K.; Tian, Y.; Erickson, J. S.; Puthoff, J.; Autumn, K.; Pesika, N. S. (Langmuir, 2012)

(untitled) - Parness, A.; Soto, D.; Esparza, N.; Gravish, N.; Wilkinson, M.; Autumn, K.; Cutkosky, M. (J. R. Soc., Interface, 2009)

(untitled) - Qu, L.; Dai, L.; Stone, M.; Xia, Z.; Wang, Z. L. (Science, 2008)

(untitled) - Ge, L.; Sethi, S.; Ci, L.; Ajayan, P. M.; Dhinojwala, A. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - Li, Y.; Zhang, H.; Yao, Y.; Li, T.; Zhang, Y.; Li, Q.; Dai, Z. (RSC Adv., 2015)

(untitled) - Majidi, C.; Groff, R. E.; Maeno, Y.; Schubert, B.; Baek, S.; Bush, B.; Maboudian, R.; Gravish, N.; Wilkinson, M.; Autumn, K.; Fearing, R. S. (Phys. Rev. Lett., 2006)

(untitled) - Varenberg, M.; Gorb, S. (J. R. Soc., Interface, 2008)

(untitled) - Gorumlu, S.; Aksak, B. (R. Soc. Open Sci., 2017)

(untitled) - Fischer, S. C. L.; Arzt, E.; Hensel, R. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Heepe, L.; Gorb, S. N. (41th Annual Meeting of The Adhesion Society, San Diego, CA, U.S.A., 25.2.2018-1.3.2018, 2018)

(untitled) - Heepe, L.; Höft, S.; Michels, J.; Gorb, S. N. (Soft Matter, 2018)

(untitled) - Heepe, L.; Carbone, G.; Pierro, E.; Kovalev, A. E.; Gorb, S. N. (Appl. Phys. Lett., 2014)

The Friction and Lubrication of Solids - Bowden, F. P.; Tabor, D. (Oxford University Press, 2001)

(untitled) - Kim, S.; Spenko, M.; Trujillo, S.; Heyneman, B.; Santos, D.; Cutkosky, M. R. (IEEE Trans. Rob., 2008)

(untitled) - Gorumlu, S.; Geikowsky, E.; Aksak, B. (Adv. Funct. Mater., 2018)